2022
DOI: 10.2337/dc21-2371
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Carotenoids With Risk of Cardiovascular Mortality Among Individuals With Type 2 Diabetes: Results From NHANES

Abstract: OBJECTIVE Although carotenoids have been suggested to exhibit antioxidant properties, some experimental studies reported that β-carotene may show pro-oxidant effects under certain conditions. Current evidence regarding the cardiovascular effects of carotenoids among patients with type 2 diabetes (T2D) is scarce. This study aimed to prospectively examine the associations of individual serum carotenoid concentrations with cardiovascular mortality among adults with T2D. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 32 publications
0
59
0
Order By: Relevance
“…Clinical trial has shown that high does β-carotene supplementation may increase lung cancer incidence in male smokers ( 46 ). Higher concentrations of serum β-carotene were significantly associated with an increased risk of cardiovascular mortality among patients with diabetes ( 47 ). For lycopene, there is no epidemiological evidence that lycopene in different concentrations exhibits the conversion between anti-oxidation and pro-oxidation properties, or harmful effects at high concentrations ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trial has shown that high does β-carotene supplementation may increase lung cancer incidence in male smokers ( 46 ). Higher concentrations of serum β-carotene were significantly associated with an increased risk of cardiovascular mortality among patients with diabetes ( 47 ). For lycopene, there is no epidemiological evidence that lycopene in different concentrations exhibits the conversion between anti-oxidation and pro-oxidation properties, or harmful effects at high concentrations ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Model 3 was additionally modified for diabetes-related factors, including diabetes duration, use of glucose-lowering medications (none, insulin, oral hypoglycemic agent, or others), history of CVD or hypertension, HbA1c level, TC level, HDL-C level, and eGFR. The multiple imputation method was utilized to impute the missing values for some covariates [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 2833 adults with diabetes aged ≥ 20 were enrolled in the NHANES III (1988–1994). The ascertainment of diabetes included a self-report of physician diagnosis, fasting plasma glucose level ≥ 7.0 mmol/L (126 mg/dL), 75-g oral glucose tolerance test result ≥ 11.1 mmol/L (200 mg/dL), or glycated hemoglobin A1c (HbA1c) level ≥ 6.5% (48 mmol/mol) [ 19 21 ]. Participants without data on serum thyroid hormone levels (n = 615), TSH and total thyroxine (TT 4 ) levels outside the reference range (n = 266), those with a history of thyroid disease at baseline (n = 110), those lost to follow-up (n = 4), and those who self-reported as being pregnant (n = 8) were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence has suggested that several nutritional biomarkers were significantly related to health outcomes. Higher serum β-carotene levels were related to lower overall and CVD mortality [ 7 , 8 ]. Serum sodium showed a U-shaped relationship with mortality [ 9 ], while both hypernatremia [ 10 ] and hyponatremia [ 11 ] were risk factors for death.…”
Section: Introductionmentioning
confidence: 99%